Autoimmune, rheumatic, chronic inflammatory diseases: Neutrophil extracellular traps on parade. (18th August 2018) - Podolska, Malgorzata Justyna; Mahajan, Aparna; Knopf, Jasmin; Hahn, Jonas; Boeltz, Sebastian; Munoz, Luis; Bilyy, Rostyslav; Herrmann, Martin
Abstract: Rheumatic diseases are a group of inflammatory conditions that affect joints and connective tissues and are often accompanied by pain and restriction of motility. In many of these diseases, autoantibodies develop that react with molecules/structures commonly found hidden in neutrophils. Neutrophil extracellular trap (NET) formation and release is considered a defense mechanism against pathogens or endogenous danger signals and it has been associated with initial inflammatory responses. NETs are also endowed with an important resolution potential based on its intrinsic enzymatic activity, but in the case they are not timely removed from the crime scene they might modulate subsequent immune responses and contribute to the pathogenesis of chronic inflammatory diseases. In this review, we will summarize the actual knowledge about the multifaceted roles of NETs in the etiology and pathogenesis of rheumatic autoimmune diseases.